Peran Aktif Taman Bacaan Masyarakat dalam Pembentukan Pengetahuan: Studi Kasus Perpustakaan Anak Bangsa, Kabupaten Malang - Septiono, Trimo; Zauhar, Soesilo; Syaifuddin, Syaifuddin (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2019)
Community library comes from community information needs. Community library was born because of dissatisfaction to information access in public library service. Community library also can support the process of community knowledge creation in the society. Perpustakaan Anak Bangsa is a community library which operates in Jabung Village Malang Disctrict since 1998. The aim of this research is to demonstrate the Perpustakaan Anak Bangsa activities in society knowledge creation process. This research used case study method with qualitative approach. The research shows that Perpustakaan Anak Bangsa’s main role is helping the process of knowledge creation by providing reading materials. In other activity, Perpustakaan Anak Bangsa makes an innovation with correlation between eduction function and recreation through user communities’ development. Perpustakaan Anak Bangsa is also active in information network.